2018
DOI: 10.1371/journal.pone.0203294
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and HIV epidemiologic profiles of men who have sex with men and transgender women in key population-led test and treat cohorts in Thailand

Abstract: Men who have sex with men (MSM) and Transgender Women (TGW) in Thailand contribute to more than half of all new HIV infections annually. This cross-sectional study describes epidemiologic profiles of these key populations (KP) in Key Population-led Test and Treat study. Baseline data were collected using self-administered questionnaires and HIV/STI testing from MSM and TGW aged ≥18 years enrolled in a cohort study in six community sites in Thailand between October 2015 and February 2016. Factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 14 publications
3
28
0
1
Order By: Relevance
“…Although greater than 5% of transgender youth age 18 to 24 years were already HIV positive, acquisition of infection appeared to rapidly accelerate to 3.5-fold by the late 20s and early 30s. This finding is similar to those of studies in Cambodia and Thailand [4,20] and consistent with a cumulative probability of being exposed to HIV over the life course [21]. The particularly steep rise in HIV prevalence from 25 to 35 may point to a critical period to intervene vigorously with behavioural and biological interventions, such as those being delivered by the "China AIDS Fund for Non-Governmental Organization" (CAFNGO) [22].…”
Section: Discussionsupporting
confidence: 87%
“…Although greater than 5% of transgender youth age 18 to 24 years were already HIV positive, acquisition of infection appeared to rapidly accelerate to 3.5-fold by the late 20s and early 30s. This finding is similar to those of studies in Cambodia and Thailand [4,20] and consistent with a cumulative probability of being exposed to HIV over the life course [21]. The particularly steep rise in HIV prevalence from 25 to 35 may point to a critical period to intervene vigorously with behavioural and biological interventions, such as those being delivered by the "China AIDS Fund for Non-Governmental Organization" (CAFNGO) [22].…”
Section: Discussionsupporting
confidence: 87%
“…This study is a sub‐study of KP‐led Test and Treat study. In 2015, we initiated a prospective observational cohort study for the KP‐led Test and Treat study with six community‐based clinic sites throughout Thailand: RSAT Bangkok, SWING Bangkok, SWING Pattaya, Sisters (Pattaya), Caremat (Chiang Mai) and RSAT Songkhla . The primary objectives of the study were to determine the proportion of first‐time HIV testers and median CD4 count at HIV diagnosis among MSM and TGW receiving KP‐led Test and Treat services, as well as to determine the uptake of early CD4 count testing through point‐of‐care CD4 and ART initiation through KP‐led support of ART linkages.…”
Section: Methodsmentioning
confidence: 99%
“…The low HIV testing uptake among MSM and TGW may stem from several problems: Thai population has a stigmatizing attitude towards people living with HIV , which may generate fear of HIV stigma and being labelled as HIV positive, thereby preventing people from seeking out their HIV status ; systematic discrimination and stigma based on gender and sexual orientation, for instance in healthcare setting, can also deter some MSM and TGW from visiting healthcare provider and getting HIV testing . Despite the efforts to make HIV testing, treatment, and prevention services more approachable to MSM and TGW using an active case‐finding Reach‐Recruit‐Test‐Treat‐Retain approach by KP‐led community‐based organizations , low uptake of HIV testing among MSM and TGW persists and may be attributed to the false premise that they are not at risk of HIV acquisition . Several studies have reported that the major reason provided by those who refused to take an HIV test was that they did not perceive themselves to be at risk .…”
Section: Introductionmentioning
confidence: 99%
“…Transgender women (TGW) are heavily burdened by HIV infection, with an estimated prevalence of 19.1% and a 49‐fold increased risk of HIV acquisition compared to general population . While studies often subsume TGW within the men who have sex with men (MSM) population, TGW typically do not consider themselves as MSM, and hold unique and distinct medication exposure, social and behavioural characteristics compared to MSM, including lower education, lower income levels, higher proportion of engaging in sex work, and the use of feminizing hormone therapy (FHT) .…”
Section: Introductionmentioning
confidence: 99%